Dynamic co-evolution of transposable elements and the piRNA pathway in African cichlid fishes - Miguel Vasconcelos Almeida; Moritz Blumer; Chengwei Ulrika Yuan; Pío Sierra; Jonathan L. Price; Fu Xiang Quah; Aleksandr Friman; Alexandra Dallaire; Grégoire Vernaz; Audrey L. K. Putman; Alan M. Smith; Domino A. Joyce; et al. (Genome Biology)
Abstract Background East African cichlid fishes have diversified in an explosive fashion, but the (epi)genetic basis of the phenotypic diversity of these fishes remains largely unknown. Although transposable elements (TEs) have been associated with phenotypic variation in cichlids, little is known about their transcriptional activity and epigenetic silencing. We set out to bridge this gap and to understand the interactions between TEs and their cichlid hosts. Results Here, we describe dynamic patterns of TE expression in African cichlid gonads and during early development. Orthology inference revealed strong conservation of TE silencing factors in cichlids, and an expansion of piwil1 genes in Lake Malawi cichlids, likely driven by PiggyBac TEs. The expanded piwil1 copies have signatures of positive selection and retain amino acid residues essential for catalytic activity. Furthermore, the gonads of African cichlids express a Piwi-interacting RNA (piRNA) pathway that targets TEs. We define the genomic sites of piRNA production in African cichlids and find divergence in closely related species, in line with fast evolution of piRNA-producing loci. Conclusions Our findings suggest dynamic co-evolution of TEs and host silencing pathways in the African cichlid radiations. We propose that this co-evolution has contributed to cichlid genomic diversity.